V-005 A CASE SERIES DEMONSTRATING APPLICABILITY OF LAPAROSCOPIC MANAGEMENT OF STRANGULATED OR INCARCERATED HERNIAS IN EMERGENCY GENERAL SURGERY. (13th October 2022) - Latif, J; Bandlamudi, N; Bhatti, I; Awan, A; Brazkiewicz, M
Abstract: Aims: Acute small bowel obstruction secondary to strangulated hernias is a presentation often encountered during the acute surgical take. Despite the widespread use of a minimally invasive approach for elective hernia surgery, there is a significant reduction in use of laparoscopy in the emergency setting. We aim to describe a case series on the applicability of laparoscopy in the management of emergency strangulated or incarcerated hernias. Materials: We describe 4 cases of patients who presented with acutely strangulated or incarcerated hernias as an emergency to a single centre in the United Kingdom. The cases demonstrated include inguinal, femoral, obturator and spigelian hernias, each presenting as an acute emergency with concomitant small bowel obstruction. Results: The patients underwent emergency surgery using a laparoscopic approach for repair of strangulated or incarcerated hernias and assessment of obstructed small bowel. Where indicated, small bowel resection and primary anastomosis was undertaken when viability of affected segment of bowel was compromised. All procedures were completed laparoscopically, with no recurrence occurring in these patients during the follow-up period. Conclusion: Minimally invasive surgery is an important tool in the armamentarium of the acute care surgeon. A laparoscopic approach will reduce the insult of intervention in already physiologically deplete patients. This case series demonstrates the feasibility of laparoscopy in the management of strangulated or incarcerated hernias in the emergent setting, requiring advanced laparoscopic skill as demonstrated in this video.